Computer-assisted method for compiling a blood group register. Issue 2 (March 1969) - Bellchambers, L. A.; Rinsler, M. G.; Signy, A. G.
Abstract : The compilation of the records of a serology department using a computer to produce alphabetically ordered files is described. This has proved to be an efficient and economical technique which may well be applied to other similar problems in a large clinical laboratory.